Design of Web-Based Planned Referral Information System from Public Health Centers to Hospital - Nugraha, Ega; Arso, Septo Pawelas; Prasetijo, Agung Budi (Unnes Journal of Public Health)
The health service referral system is the implementation of health services that regulate where and where a person with a particular health disorder should be checked for illness. Problems that occur in the referral process such as not having the certainty of service time, the service is not in accordance with the competence and the closest radius of the patient's location so that it can cause inconvenience. The aim of the study was to create a web-based planned referral system (SIJUNA) to help manage referral services from public health centers to hospitals so that there was no reason for patients not to be served because the human resources and facilities needed were not available. This research uses action research with a qualitative approach and the system development stage using the FAST method. The system is tested using black box testing so that it can be seen that the whole feature has a function that is good and in accordance with the objectives of the system user. The results of this study are the establishment of a Planned Referral Information System (SIJUNA) that facilitates the referral process of patients from the Public Health Center to the Hospital. With the existence of SIJUNA, the operational needs of services are good with the types of outpatient referrals, inpatient care, and emergencies can be fulfilled by increasing accessibility such as certainty of service time with competence and the closest radius of the patient's location, equalizing and increasing the effectiveness of health services. nearest health who has competencies according to patient needs.